PELATIHAN PENINGKATAN KETERAMPILAN GURU PAUD DALAM PENGGUNAAN APLIKASI EDMODO - Mujtahidin, Samsul; Wathoni, Hizbul (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Edmodo is a free e-learning website that can be used by educators to serve as a medium for implementing e-learning learning strategies. The aim of holding this training is to introduce PAUD teachers to the use of learning strategies using the Edmodo application and provide training as well as learning practice using a micro blogging website based on the Edmodo application. This activity was carried out using three methods, namely lecture, question and answer, and practice. The results of this activity were that the participants felt they had gained new insight into the use of e-learning in the teaching and learning process, moreover e-learning could be an alternative to learning processes that cannot be held in the classroom. Apart from that, the service participants were very happy and satisfied with the service activities and requested that similar service activities be carried out on an ongoing basis considering that this e-learning training really helps teachers in making the teaching and learning process in the classroom more varied and innovative.